A review of evaluation outcomes of web-based continuing medical education - Curran, Vernon R; Fleet, Lisa (Medical education, 2005)
Introduction  The Internet and worldwide web have expanded opportunities for the provision of a flexible, convenient and interactive form of continuing medical education (CME). Larger numbers of doctors are accessing and using the Internet to locate and seek medical information. It has been suggested that a significant proportion of this usage is directly related to questions that arise from patient care. A variety of Internet technologies are being used to provide both asynchronous and synchronous forms of web‐based CME. Various models for designing and facilitating web‐based CME learning have also been reported. The purpose of this study was to examine the nature and characteristics of the web‐based CME evaluative outcomes reported in the peer‐reviewed literature. Methods  A search of Medline was undertaken and the level of evaluative outcomes reported was categorised using Kirkpatrick's model for levels of summative evaluation. Results  The results of this analysis revealed that the majority of evaluative research on web‐based CME is based on participant satisfaction data. There was limited research demonstrating performance change in clinical practices and there were no studies reported in the literature that demonstrated that web‐based CME was effective in influencing patient or health outcomes. Discussion  The findings suggest an important need to examine in greater detail the nature and characteristics of those web‐based learning technologies, environments and systems which are most effective in enhancing practice change and ultimately impacting patient and health outcomes. This is particularly important as the Internet grows in popularity as a medium for knowledge transfer.